Educación Interprofesional, fundamentos y estrategias didácticas: revisión del estado del arte: Educación Interprofesional en el sector salud - Dueñas Darzón, Adriana Lucía
Interprofessional Education - EIP - is presented as a need of the health sector and training institutions, as an imperative centered on the patient, family and community, which will affect the quality of care and decrease adverse events. The objective of the review is to know how the EIP has generated interest in bibliographic production. Terms of reference, antecedents, advantages, difficulties and limitations are established, as well as the most frequently referenced didactic strategies in their implementation and the challenge for their integration from the technical level.